Search engine optimization as a strategy and its effectiveness in positioning retail brands in Peru - Linares-Cazola, José; Pantigoso-Leython, Nathalí (Frontiers in Communication, 2025)
This study focuses on the effectiveness of the Search Engine Optimization (SEO) strategies in increasing the positioning of retail brands in Peru. The study used a mixed approach, with consumer focus groups to analyze browsing trends. For SEO metrics were taken from: majestic.com, gtmetrix.com, sitioweb.grader.com, among others. A total of 642 questionnaires were administered, validated by Cronbach’s alpha of 0.948. The analysis using the multiple ordinal regression model allowed us to examine the positioning of SEO as a strategy to improve the CBP (Classic Brand Positioning). The findings reveal that both strategies are not dependent, but complementary. The SEO can be a powerful tool for increasing a brand’s initial visibility, while CBP ensures that such visibility translates into long-term trust and loyalty. SEO is more tactical and results-oriented, while CBP builds value over time. Finally, both strategies can be integrated. It would be a combination strategy of SEO to complement with real positioning marketing in the mind of the consumer.